Impact of Workplace Stress on Addictive Behaviors among Workers in a Tunisian Petroleum Industry - Rmadi, Nehla; Kotti, Nada; Hajjaji, Mounira; Kchaou, Amel; Hammami, Kaouthar Jmal (Addicta: The Turkish Journal on Addictions, 2025)
Occupational stress is one of the major health hazards of the modern workplace. It has been linked to a poor mental health and increased rates of addictive behaviors on and off the job. This remains relatively unexamined, especially in the Tunisian working environment, where it is the first time that this specific issue is being studied. The objective was to investigate and explore the correlation amid occupational stress, healthrelated behaviors of smoking/alcohol usage, and caffeine consumption among Tunisian onshore oil workers. A cross-sectional survey was conducted among 94 onshore oil installation workers of a Tunisian private oil company over a period of 6 months from January to June 2018. They were investigated with a self-administrated questionnaire about sociodemographic characteristics and health-related behaviors. Workplace stress was evaluated with job content questionnaire. Smoking dependence was assessed via the Fagerström score and the motivation to quit by Richmond test. Alcohol consumption was measured by the questionnaire of fast alcohol consumption evaluation. Data were analyzed using SPSS and p < .05 was considered statistically significant. This cross-sectional study included exclusively male workers with an average age of 41.17 years. The majority of employees were married (72.6%). Almost the half had a high level of education. An average of professional seniority was about 14.03 years. Of 94 workers, 33 (35.1%) were current smokers and 18 (18.9%) were current drinkers. The average caffeine consumption was 277.22 ± 153.638 mg/day. Job strain and iso-strain were respectively noted in 48.9% and 27.7%. The statistical analysis indicated that current smoking was significantly associated with low social support with an OR = 2.65 (95% CI [1.034–6.802]). The findings indicate that a substantial proportion of workers experience high levels of job strain and iso-strain, with 48.9% and 27.7%, respectively. These conditions are known to contribute to adverse health outcomes, including mental health issues and increased addictive behaviors. The significant association between low social support and current smoking (OR = 2.65) underscores the role of psychosocial factors in addictive behaviors. This aligns with existing literature that suggests individuals under stress may resort to smoking as a coping mechanism, reflecting a broader trend observed in various occupational settings. The prevalence of smoking (35.1%) and alcohol consumption (18.9%) among the participants is concerning, particularly given the high-stress environment of the oil industry. These behaviors not only pose direct health risks but can also impair job performance and safety. These data provide evidence that petroleum workers are exposed to a monotonous lifestyle in the workplace, leading to high psychosocial risks. In response to varying levels of stress, employees may adopt different addictive behaviors. All above mentioned factors can directly or indirectly threaten the workers’ health and work productivity.
Keywords: Addictions to alcohol; addictions to tobacco; occupational stress; onshore oil workers; social support